2021
DOI: 10.3390/en14102889
|View full text |Cite
|
Sign up to set email alerts
|

Effective Method for Diagnosing Continuous Welded Track Condition Based on Experimental Research

Abstract: The correct operation of the continuous welded track requires diagnosing its condition and preparation of track metrics requiring measurements of displacements of rail under operation. This is required as there are additional thermal stresses in the rails with values depending on the temperature changes of the rails. Therefore, the climatic conditions are important. This paper presents the original effective analytical method for diagnosing the condition of continuous welded track based on experimental researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The selection of rolling stock for the implementation of tasks is one of the elements of planning the railway transport system [36][37][38][39][40]. As already mentioned in the previous point of the article, it is required that a timetable be ordered from the infrastructure manager in order to be able to physically move cargo via rail transport within the railway network [41]. A few necessary parameters need to be specified while placing an order.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The selection of rolling stock for the implementation of tasks is one of the elements of planning the railway transport system [36][37][38][39][40]. As already mentioned in the previous point of the article, it is required that a timetable be ordered from the infrastructure manager in order to be able to physically move cargo via rail transport within the railway network [41]. A few necessary parameters need to be specified while placing an order.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is found that the limit lateral resistance depends neither on the chosen experimental technique, nor on the compaction level of the ballast bed, whereas the peak lateral resistance appears to be dramatically altered if it is evaluated by mean of the Single Tie Push Test. The paper [40] presents an effective analytical method for diagnosing the condition of continuous welded track based on experimental measurements. The method allows for an appropriate repair or maintenance recommendation.…”
Section: Review Of the Current Studiesmentioning
confidence: 99%
“…An important role in preventing damage propagation in CWR is the regular monitoring of the geometry and temperature condition of the rails [11], [12]. Kukulski et al in [13] presented an effective analytical method for diagnosing the condition of CWR based on experimental measurements. Supporting the decision process in the area of track repair or maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting the decision process in the area of track repair or maintenance. In addition, in [13] they recognise that in the case of a CWR, the costs of its maintenance are about 25% lower than those of a classic track. There is also significantly less wear and tear on vehicles and traction energy consumption, with better ride smoothness and less noise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation